2020
DOI: 10.3390/jpm10040216
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Perceived Barriers toward Genetic Testing and Pharmacogenomics among Healthcare Workers in the United Arab Emirates: A Cross-Sectional Study

Abstract: In order to successfully translate the scientific models of genetic testing and pharmacogenomics into clinical practice, empowering healthcare workers with the right knowledge and functional understanding on the subject is essential. Limited research in the United Arab Emirates (UAE) have assessed healthcare worker stances towards genomics. This study aimed to assess healthcare workers’ knowledge and attitudes on genetic testing. A cross-sectional study was conducted among healthcare workers practicing in eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 76 publications
4
18
1
Order By: Relevance
“…These findings may reflect pharmacists curiosity especially young and under training towards the studied topic in comparison to physicians and other respondents. Our results were similar to previous studies conducted in UAE and Qatar, [ 23 , 24 ] yet distinct from those reported in a prior study in Kuwait [ 20 ], where most participants were males and physicians.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings may reflect pharmacists curiosity especially young and under training towards the studied topic in comparison to physicians and other respondents. Our results were similar to previous studies conducted in UAE and Qatar, [ 23 , 24 ] yet distinct from those reported in a prior study in Kuwait [ 20 ], where most participants were males and physicians.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the influence of the profession was more significant in the knowledge of PGx in particular but not towards PGx testing awareness for which the experience had a larger impact. Furthermore, our findings demonstrated that younger age and less experienced professionals had the highest PGx knowledge, these results are in line with the study of Rahma et al [ 23 ] however they are inconsistent with the findings of some previous studies [ 20 , 24 ] where the influence of experience was dominant.…”
Section: Discussioncontrasting
confidence: 62%
“…Furthermore, many participants were unaware that Plavix ® (clopidogrel) PGx testing was available. A survey of healthcare workers in the Emirate found that their knowledge of PGx is fair, 41 which is similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, with pre-emptive testing, delays would not be an issue anymore. The other results concerning the risks are consistent with foreign studies among psychiatrists [ 26 , 30 ] and various health workers [ 44 ].…”
Section: Discussionsupporting
confidence: 88%